Identification of Canonical Tyrosine-dependent and Non-canonical Tyrosine-independent STAT3 Activation Sites in the Intracellular Domain of the Interleukin 23 Receptor - Floss, Doreen M. (American Society for Biochemistry and Molecular Biology, 2013)
Signaling of interleukin 23 (IL-23) via the IL-23 receptor (IL-23R) and the shared IL-12 receptor β1 (IL-12Rβ1) controls innate and adaptive immune responses and is involved in the differentiation and expansion of IL-17-producing CD4(+) T helper (T(H)17) cells. Activation of signal transducer and activator of transcription 3 (STAT3) appears to be the major signaling pathway of IL-23, and STAT binding sites were predicted in the IL-23R but not in the IL-12Rβ1 chain. Using site-directed mutagenesis and deletion variants of the murine and human IL-23R, we showed that the predicted STAT binding sites (pYXXQ; including Tyr-504 and Tyr-626 in murine IL-23R and Tyr-484 and Tyr-611 in human IL-23R) mediated STAT3 activation. Furthermore, we identified two uncommon STAT3 binding/activation sites within the murine IL-23R. First, the murine IL-23R carried the Y(542)PNFQ sequence, which acts as an unusual Src homology 2 (SH2) domain-binding protein activation site of STAT3. Second, we identified a non-canonical, phosphotyrosine-independent STAT3 activation motif within the IL-23R. A third predicted site, Tyr-416 in murine and Tyr-397 in human IL-23R, is involved in the activation of PI3K/Akt and the MAPK pathway leading to STAT3-independent proliferation of Ba/F3 cells upon stimulation with IL-23. In contrast to IL-6-induced short term STAT3 phosphorylation, cellular activation by IL-23 resulted in a slower but long term STAT3 phosphorylation, indicating that the IL-23R might not be a major target of negative feedback inhibition by suppressor of cytokine signaling (SOCS) proteins. In summary, we characterized IL-23-dependent signal transduction with a focus on STAT3 phosphorylation and identified canonical tyrosine-dependent and non-canonical tyrosine-independent STAT3 activation sites in the IL-23R.